The formation of professional knowledge competence by means of micro-group discussions as part of team-based learning - Kucher, T. V.; Кучер, Тетяна Володимирівна (My University, 2024)
The main task of higher education at the present stage is to prepare students who are able not only to obtain certain theoretical knowledge, but also to master the skills of applying the acquired knowledge in specific situations.
Keywords: тези доповідей